Performance analysis of dye solar cell with additional TiO2 layer under different light Intensities - Mohamed, N.M. (Elsevier Ltd, 2015)
Deployment of dye solar cells (DSCs) for building integration application would require a highly efficient solar cell that work well in diffused light. In order to improve the efficiency of dye solar cell, an additional layer of ultrathin anatase titanium dioxide (TiO2) has been deposited for strengthening the adhesion of the porous TiO2-based photo electrode to the conductive transparent substrate, which can lead to an enhancement in electron transportation. Fabricated cells of 1 cm2 area were tested under different light intensities (100, 33 and 10 mW cm-2) and characterized by scanning electron microscopy (SEM), Raman spectroscopy and electrochemical impedance spectroscopy (EIS). Analysis showed an increment in overall quantum conversion efficiency (Î·), as high as 35 compared to the standard cell without the additional layer of TiO2. EIS analysis has proven that the additional ultrathin anatase layer has improved the collection efficiency (Î¦COLL) as the result of the enhancement in both electron transport and lifetime within the porous TiO2 film which translated into better conversion efficiency of DSCs. Â© 2015 Elsevier Ltd. All rights reserved.